DESAIN DAN UJI COBA E-MODUL KIMIA BERBASIS PROBLEM SOLVING PADA MATERI LARUTAN PENYANGGA UNTUK KELAS XI SMA SEMESTER II: E-Modul Kimia - Indah Julia (UIR Press, 2020)
Abstract The background of this research is due to the limited learning resources that are independent and the lack of learning resources that the connect of material with daily life.Thus, in this research it was designed a design and test of Problem-Solving based chemistry E-Module using Kvisoft Flipbook software on Buffer Solution lesson.This research was administered at SMA PGRI Pekanbaru. 4D development model was used in this research until Develop stage. The subjects of this research were a material validation, a media validation, and 1 teacher at the SMA PGRI Pekanbaru and 1teacher at the SMAN 5 Tapung to test the media practicality, and 10 students of SMA PGRI Pekanbaru were to know the response of the media to know the response of the media.The data were collected through interview and questionnaire. The obtained data then were analyzed by using qualitative and quantitative descriptive analysis techniques. Based on the research finding, it was obtained the assessment on material aspects 98.33% and by the media 95%, and they were on very valid criterion.The assessment percentage of student practicality test was 92.8% and the teacher was 93.5%, they were on very practical criterion. Keywords: E-Module, Problem Solving Approach, Kvisoft Flipbook, Buffer Solution